(untitled) (Journal of Asian Development Studies, 2020)
The main aim of the study was to identify the causes of conflict between the family and work lives of married female teachers of the universities in Pakistan’s patriarchal society. This study was qualitative in nature. Semi-structured interviews were conducted to explore the causes of role conflict at work place among married female university teachers. Three public sector universities, University of the Punjab, Lahore College for Women University and University of Education, were selected as sample. Sixty female teachers were interviewed. The interviews were audio recorded then transcribed and coded for emerging themes and categories. The analysis of the data revealed that women experienced role conflict as a result of simultaneity of their multiple roles. Extended working hours at university has a great contribution in generating work-family conflict.